Impact of parenchymal preserving surgery on survival and recurrence after liver resection for colorectal liver metastasis. Issue 1 (25th April 2016) - Pandanaboyana, Sanjay; Bell, Richard; White, Alan; Pathak, Samir; Hidalgo, Ernest; Lodge, Peter; Prasad, Raj; Toogood, Giles
Abstract : Background: This study aimed to investigate the impact of non‐anatomical liver resection (NAR) versus anatomical resection (AR) in patients with colorectal liver metastasis (CRLM), with regard to perioperative and long‐term outcomes. Methods: Analysis of prospectively collected data for patients with CRLM who underwent either AR or NAR between January 1993 and August 2011 was performed. The impact of AR and NAR on morbidity, mortality, margin positivity, redo liver resections, overall survival (OS) and disease free survival (DFS) was analysed. Results: A total of 1574 resections for CRLM were performed. A total of 249 were redo resections and 334 patients underwent combined AR and NAR, hence, 583 were excluded. In total, 582 AR and 409 NAR were performed. The median age was 66 years (range 23.8–91.8). Median follow up was 32.2 months (interquartile range 17.5–56.9). The need for postoperative transfusion (11.6% versus 2.2%, P = <0.0001), overall complications (25% versus 10.7%, P < 0.0001) and 90‐day mortality (4.9% versus 1.2%, P < 0.0001) was higher in the AR group. R0 and R1 resection rates (AR 26.2% NAR 25%, P = 0.69) and number of patients with intrahepatic recurrence was similar between the two groups (AR 17.5% NAR 22%, P = 0.08). However, the need for redo liver surgery was higher in NAR group 15.4% versus 8.7% ( P < 0.001). The OS (NAR 34.1 months versus AR 31.4 months, P = 0.002) and DFS were longer in the NAR group (NAR 18.8 months versus AR 16.9 months, P = 0.031). Conclusions: A parenchymal preserving surgery (NAR) is associated with lower complication rates and better OS and DFS when compared with AR without compromising margin status. However, NAR increases the need for repeat liver resections.